The Slovene language in Carinthia - symbolic bilingualism - Reiterer, Albert F. (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
Questions for the "colloquial language" are put at every census in Austria since World War II, and in fact since the census of 1880 in Cisleithania. The last one of the year 2001 resulted in about 12.600 Austrians (respectively 14.000 inhabitants) in Carinthia "confessing" - this is the term used most often - to speak Slovene. However, as it is well known to all experts, the census term of "colloquial language" is understood in a way other then indicating linguistic skills or everyday use of the language, that is, signifying the readiness to identify ethnically (politically) with the Slovene minority. This is demonstrated best by comparing the numbers of the census with an investigation looking exclusively for linguistic skills. A representative survey in annex to a micro-census and lead by the author in September 1999 resulted in about 60.000 persons aged 15 years or more speaking or understanding Slovene. The following presentation gives some of the results of this survey in more detail, and it gives some hints at the contexts in which Slovene in Carinthia is spoken, according to this investigation. It discusses the difference between the two numbers and ask for the meaning of ticking in "Slovene" in the census questionnaire, in contrast to the everyday use or the capability to understand the minority language. Following the concept of symbolic ethnicity, coined by H. J. Gans (1979) and tested empirically by R. D. Alba (1990) for the U.S.A., it is argued that bilingualism in Austria - not only with the Slovenes, but with the Burgenland-Croats and the Magyars, too - gets always more a symbolic and less a pragmatic value for the members of the respective linguistic minorities in this country. To the term of symbolic ethnicity the term of symbolic bilingualism has to be added. Supposedly, this loss of structural value while maintaining an identitarian value of the most used indicator for ethnic affiliation in West and Central Europe is the course of post-modern ethnicity in Western Europe and in politically highly developed countries, at least, if the concerned are minority groups.
Keywords: Austria; Avstrija; narodne manjšine; jezikovne manjšine; koroški Slovenci; Carinthian Slovenes; narodna identiteta; dvojezičnost; bilingualism; Slovene; slovenščina; German; nemščina